Implementasi Reward Dan Punishment Terhadap Produktivitas Karyawan KSPPS BMT Surya Raharja Cabang Panceng - Haqiqotur Rohaniah; Anugrahini Irawati (Management Department of Economics and Business Of Trunojoyo Madura University, 2023)
An organization cannot survive and run without employees or human resources in it. Employee productivity will determine whether the company can grow or not. In other words, the achievement of the organization is very dependent on employee productivity, this hope is of course encouraged and supported by management that can support employee performance so that it is better. Therefore, it’s important to implement rewards and punishments for employees. This study aims to determine the implementation of reward and punishment on employee productivity in the KSPPS BMT Surya Raharja Panceng Branch. The research method used in this research is a descriptive qualitative method. Data collection was carried out by observing, in depth interviews, and documentation. The results of this study indicate that the implementation of reward and punishment has a positive impact on the productivity of BMT Surya Raharja employees. This positive impact is shown by employees who are more enthusiastic at work and improve their performance both in financing and savings. With the implementation of reward and punishment employee productivity is increasing. This is evidenced by employees who achieve targets every month. So it can be concluded that the implementation of reward and punishment affects employee productivity.